Software Project Management: A Process-Driven Approach - Ahmed, Ashfaque (Auerbach Publications, 2012)
Written for practitioners and students of software testing and quality assurance, this book covers all of the necessary concepts and techniques. The first part deals with software testing, while the second part covers software quality assurance. It covers standards issued by the IEEE, the ISO, and the Software Engineering Institute. The author details all of the processes, metrics, techniques, and standards for testing and quality assurance. To add practical knowledge, the book includes case studies showing applications and real-world use. It also includes challenging practice questions and solutions.